Anaphora in the Interlanguage of Spanish Learners of English - Elisa Vázquez Iglesias (Miscelánea - Departamento de Filología Inglesa y Alemana, Universidad de Zaragoza, 1998)
Much work has been done lately on the acquisition of English reflexives by L2 learners (cf. Matsumura [1994], Bennet [1996] or Wakabayashi [1996], among others). The aim of this paper is twofold: first, to examine an experiment that has been carried out with Spanish learners of English and, second, to show how imprecise the conclusions that we may reach from this type of experiments are. Thus, while previous work on Japanese and Serbo-Croatian seems to indicate that Second Language Acquisition is systematic and, further, that Universal Grammar is available in acquisition, I suggest that the results obtained in the experiment reported in this paper lead to the opposite claims.